2015
DOI: 10.1017/s0033291715001439
|View full text |Cite
|
Sign up to set email alerts
|

Reduced contextual effects on visual contrast perception in schizophrenia and bipolar affective disorder

Abstract: Background The salience of a visual stimulus is often reduced by nearby stimuli, an effect known as surround suppression of perceived contrast, which may help in locating the borders of an object. Weaker surround suppression has been observed in schizophrenia but it is unclear whether this abnormality is present in other mental disorders with similar symptomatology, or is evident in people with genetic liability for schizophrenia. Methods By examining surround suppression among subjects with schizophrenia or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 64 publications
9
75
1
1
Order By: Relevance
“…It is consequently not a gross over-simplification to assert that depth inversion illusions are by-and-large normal in bipolar disorder and more common in schizophrenia. This conclusion is broadly consistent with other behavioral investigations which have documented either intermediate or absent visual deficits in bipolar disorder (Jahshan et al, 2014; Kéri et al, 2005b; Schallmo et al, 2015; Yang et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…It is consequently not a gross over-simplification to assert that depth inversion illusions are by-and-large normal in bipolar disorder and more common in schizophrenia. This conclusion is broadly consistent with other behavioral investigations which have documented either intermediate or absent visual deficits in bipolar disorder (Jahshan et al, 2014; Kéri et al, 2005b; Schallmo et al, 2015; Yang et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Another important perceptual function for navigating the visual world involves the modulation of a central stimulus by the presence and configuration of surrounding stimuli; typically, more similar surrounding contexts reduce perceptual salience (i.e., surround suppression; (Chubb et al 1989;Snowden & Hammett 1998;Xing & Heeger 2000Yu et al 2001Yu et al , 2003 ). Effects of surrounding context are thought to be weaker in SCZ; for example, surround suppression during contrast perception is weaker in SCZ vs. healthy control subjects (Dakin et al 2005;Yoon et al 2009;Tibber et al 2013;Yang et al 2013a;Schallmo et al 2015) , and similar effects have been reported during contour detection (Schallmo et al 2013) .…”
Section: Introductionmentioning
confidence: 92%
“…To date, the extent to which impaired contour integration and weaker context modulation are specific to patients with schizophrenia, as compared to patients with bipolar disorder (BP) is unclear (Yang et al 2013b;Schallmo et al 2015) . Schallmo and colleagues (24) reported weakened surround suppression effects in both schizophrenia and bipolar disorders as compared to controls (CON), although SCZ exhibited more profound deficits than BP.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between group and stimulus condition was not statistically significant, providing no evidence for altered orientation-dependent contextual modulation of contrast perception in schizophrenia. Finally, there is also a relevant study by Schallmo et al (2015) in which the primary dependent variable was the contrast by which an isolated target needed to be adjusted in order to perceptually match the contrast of an adjacent target that was embedded in an articulated spatial context. The interaction between group (those with and without a diagnosis of schizophrenia) and stimulus condition (parallel and orthogonal surround) was not statistically significant.…”
Section: Evaluating the Evidence For The Effect In Schizophreniamentioning
confidence: 99%
“…Manuscript to be reviewed Visual contextual modulation, in which the perception of a target stimulus is affected by the presence of a surrounding stimulus, has received considerable investigation in those with schizophrenia (Barch et al, 2012;Dakin et al, 2005;Tibber et al, 2013;Yang et al, 2013, for example). The orientation-dependent surround effect is a specific instance of contextual modulation that has been used to examine visual processing in those with schizophrenia (Schallmo et al, 2015;Serrano-Pedraza et al, 2014;Seymour et al, 2013;Yoon et al, 2009), and is particularly relevant due to its well-established behavioural and neural foundations. In this approach, a target pattern is surrounded by a similar pattern of either the same orientation (parallel) or the orthogonal orientation.…”
Section: Introductionmentioning
confidence: 99%